Growth arrest‐specific 5 attenuates cisplatin‐induced apoptosis in cervical cancer by regulating STAT3 signaling via miR‐21. Issue 6 (23rd October 2018) - Yao, Tingting; Lu, Rongbiao; Zhang, Jun; Fang, Xingyu; Fan, Li; Huang, Chunxian; Lin, Rongchun; Lin, Zhongqiu
Abstract: Cervical cancer is the most common cause of female cancer‐related mortality worldwide. Decreased expression of long noncoding RNA growth arrest‐specific 5 (GAS5) is found in human cervical cancer tissues and associated with poor prognosis. However, the studies on associations between GAS5 level and malignant phenotypes, as well as sensitivity to chemotherapeutic drug in cervical cancer cells are limited. In this study, overexpression of GAS5 in cervical cancer cells resulted in prohibited cell proliferation and colony formation, which were promoted by siGAS5. Enhanced GAS5 increased cell percentage in the G0/G1 phase and decreased cells percentage in the S phase, whereas reduced expression did not. The malignant behaviors of cervical cancer cells, manifested by cell migration and invasion, could be weakened by the GAS5 overexpression and enhanced by siGAS5. Furthermore, in cisplatin‐induced cell, overexpression of GAS5 reduced cells viability and enhanced apoptosis, whereas in cells transfected with siGAS5, apoptosis eliminated. We have reported the upregulation of microRNA‐21 (miR‐21) and its oncogenetic roles in cervical cancer previously. In this study, we found the negative relationship between the GAS5 and miR‐21. Moreover, the decrease of miR‐21 associated proteins phosphorylated STAT3 and E2F3 was seen in GAS5 overexpressed cells, both of which could be increased by siGAS5. The GAS5 deficiency also reduced miR‐21 target proteins TIMP3 and PDCD4 expressions. Taken together, the GAS5 expression level is inversely associated with malignancy, but positively associated with sensitivity to cisplatin‐induced apoptosis, suggesting that GAS5 could be a biomarker of cisplatin‐resistance in clinical therapy of human cervical cancer. Abstract : Growth arrest‐specific 5 (GAS5) is associated with malignancy of cervical cancer GAS5 attenuates cisplatin‐induced apoptosis in Hela cells by promoting STAT3 signaling GAS5 has relationship with miR‐21 in cervical cancer.